EFFECTS OF SODIUM BUTYRATE USE IN PIGS PERFORMANCE IN THE INITIAL STAGE - C. G Czechowski (Scientific Electronic Archives, 2017)
While passing of the years the pigs production intensified and with that the reduction of the age of weaning characterized for the most critical phase regarding the food handling interfering in the reduction of the consumption of food and consequently in the daily middle profit. The handling carried out incorrectly can provoke intestinal problems, for example, the diarrhea. In decades one used antibiotics to reduce the harmful effects of the intestinal microflora, in order to improve the performance of the animals however his frequent use provided the appearance of patógenos resistant. By this reason substances were created with potential to substitute the antibiotics between them the organic acids. In this way the objective of the work valued the effects of the butirato of sodium at the parameters of productive and economical performance of suckling pigs in the initial phase. There were used 12 suckling pigs, males and females, half-castes of the races Landrace x Large white, divided in two treatments. T1 – Treatment controls and T2 – Treatment with butirato of sodium. The used experimental delineation was it completely casualizado with three repetitions for treatment, and two animals for experimental unity. The evaluated parameters were gained of weight (GP), consumption of ration (CR), conversion to feed, consistency of the feces and the cost of the ration for kg of produced suckling pig. The performance data were subjected to the analysis of variância (ASSISTAT 7.5, 2008), being the difference between the averages checked by the test F. There was no difference (P> 0,05) between the treatments in the GP, CR, FC and in the consistency of the feces, however the addition of butirato of sodium presented the least values of cost of the ration for kg of produced suckling pig. In this way it is possible to end that the use of butirato of sodium influenced positively the economical performance of suckling pigs.